Assessing the Influence of Influencer Leadership, Digital Transformation and Social Climate on Improving Teacher Achievement in Building Excellent Madrasahs - Suci Hidayati; Munirul Abidin; Andika Harianto Subakti; Aini Rizqoh (Yayasan Adra Karima Hubbi, 2025)
Background. Achievement in the world of education is identical to the achievement of student learning outcomes in academic or non-academic fields. The focus of education tends to be on output. Purpose. The focus of the study aims to assess how much influence influencer leadership, digital transformation and social climate have on improving teacher achievement in building superior madrasas. Method. The number of respondents in the study was 124 private madrasa teachers in Malang Regency with a liket scale measurement of 1-5. Analysis. Results. The results of the study showed that: (1) There is a significant influence between influencer leadership and improving teacher achievement (2) there is a significant influence between digital transformation and improving teacher achievement and (3) there is no significant influence between social climate. Conclusion. Predictively, researchers see that psychological factors in the form of self-efficacy have a greater influence than social climate in terms of improving teacher achievement.